Association of iron deposition in MS lesion with remyelination capacity using susceptibility source separation MRI - Hyeong-Geol Shin; Woojun Kim; Jung Hwan Lee; Hyun-soo Lee; Yoonho Nam; Jiwoong Kim; Xu Li; Peter C.M. van Zijl; Peter A. Calabresi; Jongho Lee; Jinhee Jang (NeuroImage: Clinical)
Objectives: Susceptibility source-separation (χ-separation) MRI provides in-vivo proxy of myelin (diamagnetic susceptibility, χdia) and iron concentrations (paramagnetic susceptibility, χpara) in the central nervous system, potentially uncovering myelin- and iron-related pathology in multiple sclerosis (MS) lesions (e.g., demyelination, remyelination, and iron-laden microglia/macrophages formation). This study aims to monitor longitudinal changes in χpara and χdia signals within MS lesions using χ-separation and evaluate the association between lesional iron and remyelination capability. Methods: Fifty participants with MS (pwMS) were followed annually over a mean period of 3.3 years (SD = 1.8 years) with MRI, including χ-separation, and clinical assessments. To monitor lesions from their early stage (lesion age < 1 year), we identified newly-noted lesions (NNLs) and contrast-enhancing lesions (CELs), and tracked their longitudinal changes in χpara and χdia signals. Results: Twenty-three pwMS were detected with NNLs and/or CELs (38 NNLs, 31 CELs;7 overlapped). Among these lesions (62 lesions in total), 27 exhibited χpara hyperintensity, termed hyper-paramagnetic sign (HPS), indicating iron deposition “throughout” the lesion (not confined to rim sign). Early-stage HPS correlated with future remyelination failure detected by χdia myelin signals (P < 0.001). After adjustment, lesions with early HPS demonstrated an annual loss in myelin signal (−1.94 ppb/year), whereas those without early HPS exhibited annual recovery (+0.66 ppb/year). Participants with confirmed disability improvement (CDI) had fewer HPS-positive lesions at baseline than those without CDI (P < 0.001). Conclusion: The presence of HPS is associated with impaired remyelination capacity and a lack of disease improvement in pwMS. Identifying HPS may help demarcate lesions more amenable to myelin repair therapies.